Narrow Banks: An Alternative Approach to Banking Reform - Kenneth Spong (Levy Economics Institute of Bard College, 1993)
Recent banking problems have prompted a variety of proposals for reforming deposit insurance and the banking system. Nearly all of these proposals, however, suffer from a common flaw - they would fail to create a banking system that is both stable and free to respond to market forces and financial developments. Narrow banking offers a possible means for accomplishing these objectives. Narrow banking would create a stable payments system by backing transaction deposits with only those assets that are truly appropriate for this task - marketable securities with virtually no interest rate or credit risk. As a result, narrow banks would essentially be "fail-safe" institutions and could operate without the inherent weaknesses of the current system. They would not pose a risk to depositors, taxpayers, or federal authorities and, unlike commercial banks, would not require extensive governmental support and intervention. These features of narrow banks would allow market forces to guide everyday banking decisions and the activities of any affiliated firms, thus returning the market to its proper role in allocating financial services. In many respects, narrow banking mirrors another banking reform that took place in the 1860s - the use of U.S. Government securities to back national bank notes. This earlier reform and the following change to Federal Reserve Notes collateralized largely by U.S. obligations have produced a stable currency and ended any public concern about its acceptability. This success provides strong evidence that narrow banking is a workable system that could stabilize our deposit system and its transactions function. Narrow banking, much like this earlier reform, appears to involve a dramatic change in the banking system. However, recent financial trends are making narrow banking a less radical change than commonly believed. In addition, most of the other approaches to recent banking problems entail a movement toward greater regulatory and governmental control of our financial system and its credit allocation functions - a response that is unlikely to make banking a vibrant, competitive industry. All of these factors thus suggest that narrow banking deserves careful consideration in efforts to reform the financial system.
Keywords: 330